Esensi Tranformasi Sistem Sentralisasi-Desentralisasi Pendidikan Dalam Pembangunan Masyarakat - Kris Setyaningsih (El-Idare, 2017)
Country of Indonesia consisting of several islands with various culture and geography. Such diverse culture and geography have shaped each region in their unique and potential. The uniqueness and potential of the resources and life of each region. To optimize from each unique and potential owned by each region needed appropriate and competent human resources. Human resources who understand every opportunity of the uniqueness and potential of the region, especially local human resources. The way out of the fulfillment of human resources capable of supporting regional development by optimizing the uniqueness and potential is educational institutions. Referring to that the area of each region has its own unique and potential, then changed the education system that had been centralized into decentralization. Where the management of educational institutions submitted to their respective areas in particular related to the purpose of educational institutions. The purpose of the educational institution should be able to support the local development efforts.